FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN PERAWAT TERHADAP END OF LIFE DI INSTALASI GAWAT DARURAT RUMAH SAKIT SILOAM PALEMBANG TAHUN 2021 - Oscar Ari Wiryansyah (Jurnal Kesehatan dan Pembangunan, 2022)
End Of Life Care (EOLC) is part of the concept of palliative care which aims to help people with chronic diseases live their best lives until they die in good condition. The World Health Organization (WHO) states that in 2016 the global adult mortality rate was 142 per 1,000 population. The purpose of this study was to determine the factors related to nurses' knowledge of the end of life in the Emergency Room of the Siloam Hospital Palembang in 2021. The design of this study was to use quantitative analytical methods with a cross sectional approach. The sample in this study were all nurses in the emergency department at Siloam Hospital Palembang with a total sample of 28 people. The results showed that there was a relationship between nurse education (p value = 0.020), training (p value = 0.007) and experience (p value = 0.019) with nurses' knowledge about the end of life in the Emergency Room of Siloam Hospital Palembang with p value 0.020. Suggestions are expected to further increase the motivation of nurses, especially in conducting end of life. So that it is expected to improve the performance of nurses in carrying out end of life and in providing services to the community so that the quality of hospital services can be better and gain the trust of the community.